Fracturing Writing Spaces: Multimodal Storytelling Ignites Process Writing. (25th October 2013) - Lenters, Kimberly; Winters, Kari‐Lynn
Abstract: In this paper, we explore the affordances of literature‐based, arts‐infused and digital media processes for students, as multimodal practices take centre stage in an English Language Arts unit on fractured fairy tales. The study takes up the challenge of addressing multimodal literacy instruction and research in ways that utilize a range of modalities. Incorporating the perspectives and multimodal texts of five students, Alvin, Adamma, Emmett, Layla and Yacoub, we highlight the highly supportive writing environment made possible for these fifth grade learners. The oral, embodied, visual, and written group explorations of the language of fairy tales, story and parody, found in fractured fairy tales, afforded the students numerous, rich opportunities to explore and experiment with language, which ultimately led to the production of individual fractured fairy tales written with a level of sophistication their teacher had not previously seen in their writing.